„Der spielt im Moment nicht mehr ganz die Rolle“: der Hausarzt in der spezialisierten ambulanten Palliativversorgung aus Patientenperspektive - Schwabe, Sven; Ewert, Benjamin (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2016)
BackgroundThe outpatient medical care of palliative patients (PPs) has always fallen within the duties of general practitioners. Since the specialized palliative out-patient care (SAPV) legislation in 2007 palliative home care teams (PCTs) were established, providing holistic medical, nursing, and psychosocial support for patients with life-limiting illness and their care providers.ObjectivesThe article explores the role of GPs in palliative home care settings with PCTs from the patient’s perspective.Materials and methodsFrom December 2014 to January 2015 we conducted 23 qualitative, semi-structured interviews with severely ill patients receiving specialist palliative care at home in Germany. The theory-based analysis followed the qualitative content analysis according to Mayring.ResultsThe expectations of PPs towards their GP in integrated palliative care were influenced by individual criteria such as availability, intensity and duration of the doctor-patient-relationship. In relation to the quality of the long-term relationship and more specifically for basic medical care GPs still play an important role. On the other hand, PCTs are becoming increasingly important. In addition to the pain-management and symptom control responsibilities, they meet the daily care needs of PPs and their caregivers by coordinating the care network as well as providing psychosocial support and 24/7-care.ConclusionsShifting of traditional tasks from GPs to PCTs influences the role of the GP. PCTs can unburden the GP from unrealistic expectations and improve the patients’ quality of life. However, this leads to a tendency for reduced importance of the GP.